Analysis of the Implementation of Measuring Skills and Physical Futsal Sports Based Desktop Program - Gumantan, Aditya; Mahfud, Imam; Yuliandra, Rizki (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
The purpose of this study was to determine the effectiveness of the implementation of a desktop program-based skills and physical measurement tools for futsal. Seeing the level of effectiveness and level of efficiency of the time used compared to doing the test manually. The research method used is quantitative research with descriptive statistical techniques. The study population was active students in the futsal student activity unit of the Indonesian Technocrat University, amounting to 30 people with 17 men and 13 women who had good skill and physical classifications. The data collection technique used a non-test instrument, in the form of distributing questionnaires to the entire population. The results of the study found that the effectiveness of the desktop-based measuring instrument program was more than 85%, with the results that had a large percentage classification, the overall answer was that the tool could be used properly and easily. The desktop program tool has good speed and time efficiency in taking tests and gets accurate scores, students could view their scores forthwith compared to the tests that are evaluated manually, so the desktop program-based futsal measurement tool is very effective and can be used properly as a new development in the futsal sports measurement test.